Part 1: Classical Theory Books That Include Women - Thomas, Jan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The following classical theory textbooks have a chapter or more on some of the early women sociologists. This is not an exhaustive list but a place to begin. There are also textbooks on social theory spanning classical and contemporary writers which include some of the early women such as Lemert.